Strengthening smallholder producers’ skills and market access: Productive alliance programme in Chile - Castillo, Mayarí; Cazzuffi, Chiara; Chamorro, Catalina; Pérez-Silva, Rodrigo; Sandoval, Diego; Sepúlveda, Macarena; Gilbert, Rachel; Davis, Kristin E. (Food and Agricultural Organization of the United Nations, 2021)
This case study report was written as a part of the Agriculture Human Capital Investment Study, funded by FAO Investment Centre and with the support of the International Food Research Institute and the CGIAR Research Programme on Policies, Institutions and Markets (PIM) and the FAO Research and Extension Unit. This study analyses the impact of Chile´s Productive Alliance Programme (PAP) in terms of human capital development among small farmers. The programme, originally created in 2007 and serving now close to 3,600 small farmers in Chile, enhances the creation of commercial partnerships between these small farmers and larger companies, and funds and facilitates the conditions for the acquisition of skills and human capital among them to ensure its success.